Lubomír Tyllner, Zdeněk Vejvoda, „Česká lidová píseň: historie, analýza, typologie”, Praha 2019 - Przerembski, Zbigniew Jerzy (Muzyka, 2021)
Recenzja książki: Lubomír Tyllner, Zdeněk Vejvoda, Česká lidová píseň: historie, analýza, typologie, Praha 2019